Toward all-day wearable health monitoring: An ultralow-power, reflective organic pulse oximetry sensing patch - Lee, Hyeonwoo; Kim, Eunhye; Lee, Yongsu; Kim, Hoyeon; Lee, Jaeho; Kim, Mincheol; Yoo, Hoi-Jun; Yoo, Seunghyup (Science advances, 2018)
Ultralow-power organic wearable patches have been developed for all-day monitoring of heart rate and blood oxygen level. Pulse oximetry sensors have been playing a key role as devices to monitor elemental yet critical human health states. Conventional pulse oximetry sensors, however, have relatively large power consumption, impeding their use as stand-alone, continuous monitoring systems that can easily be integrated with everyday life. Here, we exploit the design freedom offered by organic technologies to realize a reflective patch-type pulse oximetry sensor with ultralow power consumption. On the basis of flexible organic light-emitting diodes and organic photodiodes designed via an optical simulation of color-sensitive light propagation within human skin, the proposed monolithically integrated organic pulse oximetry sensor heads exhibit successful operation at electrical power as low as 24 μW on average. We thereby demonstrate that organic devices not only have form factor advantages for such applications but also hold great promise as enablers for all-day wearable health monitoring systems.